CHARACTERIZATION OF NANOHYDROXYAPATITE FROM TUNA’S Thunnus sp BONE AS BIOMATERIALS SUBSTANCE - Aditya Bayu Hanura; Wini Trilaksani; Pipih Suptijah (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
Tuna Thunnus sp is a high-value fisheries products. The abundance of waste from tuna’s processing industry has not been used optimally. The objective of this study was to produce and characterize nanohidroxyapatite (Ca5(PO4)3((OH)0.8F0.2) of tuna’s Thunnus sp bone waste using high temperature sintering of 400-800OC continuing by nanomilling method. The results of the characterization showed that the sintering temperature of 800OC was the best treatment yielding of hidroxyapatite 57.73%, 89.27% white degree level. The result of statistic analysis showed that the sintering temperature variation gave a significant effect on the white degree at the test level (p <0.05). Proximate result after sintering showed moisture content of 0.15%, 99.83% ash, 0.05% fat, 0.73% protein and 0% crude fiber. Results of heavy metal analysis showed the content of lead (Pb) and mercury (Hg) was negative, and cadmium (Cd) 0.018 ppm. The mineral test consist of calcium, phosphor, kalium, magnesium, iron, zinc, manganese, and sodium with the dominant elements were 49.76% calcium and 9.02% phosphor. The result of statistic analysis showed that the sintering temperature variation gave significant effect to the three main minerals at the test level (p<0.05). The Particle Size Analyzer test showed that nanohidroxyapatite particles was measured at 800-900 nm. The X-Ray Diffractometer analysis showed the results of sample identification contains hydroxyapatite and fluorian, with syn 100.00%. The hidroxyapatite was a compound complex and crystals formed has a hexagonal shape with a percentage of 82.9% crystallinity. Keywords : bone, nanohidroxyapatite, particles, sintering, tuna